Monospecific helminth and arthropod infections in an urban population of brown rats from Doha, Qatar - Abu-Madi, Marwan A.; Lewis, John W.; Mikhail, M.; El-Nagger, M.E.; Behnke, Jerzy M. (Cambridge University Press, 2001)
Parasitic infections were studied for the first time in an urban population of brown rats (Rattus norvegicus) from Doha. Only one species of helminth was found, the cestode Hymenolepis diminuta, and one ectoparasite, the flea Xenopsylla astia, from a sample size of 136 rats (52 males and 84 females). The prevalence of H. diminuta was 17.6%, increasing with host age but not in relation to host sex nor season of capture. Host age was a key factor in influencing abundance of infection, although there was a significant three-way interaction with season and host sex arising through heavy infections in juvenile male rats in the summer. The prevalence of X. astia was 45.6%, although both prevalence and abundance of infestations were season and host age dependent. In the winter prevalence and abundance were similar in both host age and sex groups, but in the summer both parameters of infestation were markedly higher among juveniles compared with adults. We found evidence for some association between these two species: H. diminuta was more prevalent among rats with fleas than among those without, although this association was season-, and independently sex- and age-dependent. There were no quantitative interactions and reasons for this are discussed in relation to the foraging and breeding behaviour of the brown rat in Qatar.